Macroeconomic Effects of Reforms on Three Diverse Oil Exporters : Russia, Saudi Arabia, and the UK - Beidas-Strom, Samya (IMF Working Papers; Working Paper ;, 2019)
We build and estimate open economy two-bloc DSGE models to study the transmission and impact of shocks in Russia, Saudi Arabia and the United Kingdom. After accounting for country-specific fiscal and monetary sectors, we estimate their key policy and structural parameters. Our findings suggest that not only has output responded differently to shocks due to differing levels of diversification and structural and policy settings, but also the responses to fiscal consolidation differ: Russia would benefit from a smaller state foot-print, while in Saudi Arabia, unless this is accompanied by structural reforms that remove rigidities, output would fall. We also find that lower oil prices need not be bad news given more oil-intensive production structures. However, lower oil prices have hurt these oil producers as their public finances depend heavily on oil, among other factors. Productivity gains accompanied by ambitious structural reforms, along with fiscal and monetary reforms could support these economies to achieve better outcomes when oil prices fall, including via diversifying exports.